Total Jumlah Hewan Ternak Yang Dihasilkan Dari Kegiatan Peternakan Kota Pekanbaru - Zoebar, M. Arif Yutaro; Sasmita, Aryo; Edward, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The results of the study show that the total amount of CO2 emissions equivalent produced by livestock in Pekanbaru is 36.19 Gg CO2-eq/year, while agriculture sector contributes 72.26 Gg CO2-eq/year. There are, in total, 7,102,134 cattle in Pekanbaru, with the estimation of total methane (CH4) emissions from enteric fermentation of 6,64642 Gg CO2-eq/year, while from manure management is 6.60444 Gg CO2-eq/year. The direct and indirect emissions of nitrous oxide (N2O) are 117,255.74 kg CO2-eq/year, and from the manure management is 110,014.72 kg CO2-eq/year of year 2017. The research concludes the total emissions of green house gas produced by livestock and agriculture sectors as well as a course of mitigation action that can be to reduced by adaptation efforts to deal with climate change in Pekanbaru.Keywords: Green House Gas, Livestock, Agriculture, Methane